Tendencies of Withdrawal Behavior of Students Who Are Victims of Bullying at Smpn 1 Lubuk Sikaping - Dwi Cantika , Nadia; Rila Rahma Mulyani; Citra Imelda Usman (Journal of Practice Learning and Educational Development, 2026)
This research is motivated by the phenomenon of students at SMPN 1 Lubuk Sikaping who are victims of bullying and show a tendency towards withdrawn behavior. The purpose of this research is to describe the tendency towards withdrawn behavior of students who are victims of bullying in terms of individual characteristics, including (1). Often seen alone or daydreaming, (2). Seemingly unenthusiastic in daily social activities, (3). Doing whatever is ordered or requested by others even though they don't like it or don't want to, (4). Not talking much, especially in expressing their opinions in public, (5). Feeling uncomfortable and unsafe in social environments, and (6). Preferring to do things alone, even though they should be done together. This study employed a qualitative approach with descriptive data. The key informants were students (CDA and IJA), as well as four additional informants: guidance and counseling teachers (MGM and NM), and peers (RAJ and SAP). Data collection was conducted through interviews, while data analysis involved data reduction, data presentation, and conclusion drawing. The results of the study showed that students who were victims of bullying showed: (1). A tendency to separate themselves from their surroundings, (2). Decreased involvement in group activities, (3). Tendency to follow friends' orders (4). Rarely speak in public places, (5). Feeling unsafe in crowded environments, such as the school field or canteen, and (6). Preferring to work alone rather than in groups. Based on these findings, it is recommended that students need to develop courage in expressing themselves and seek support from a trusted environment to improve social skills.